Microbial transformation of sewage sludge to biolipid-based fuel using potential oleaginous bacteria Streptomyces sp. - Sana Akbar; Muzammil Anjum; Samia Qadeer; Rab Nawaz; Zepeng Rao; Zepeng Rao; Habib Ullah; Abdulaziz Alamri; Mohamed A. El-Tayeb (Frontiers in Microbiology)
IntroductionThe high proportion of sludge generation worldwide has sparked interest in utilizing it for alternative purposes. Among different potential applications, using sludge as a substrate for oleaginous bacteria is a relatively novel approach. The study was conducted to harness Streptomyces sp. to produce bio-lipids and their further processing for biofuel through transesterification.MethodsSewage sludge was obtained from the I-9 treatment plant, Islamabad; after initial characterization the unprocessed sludge was optimized viz.: incubation time (24–96 h), inoculation rate (5–15%), pH levels (4–9), temperature (25–40°C), agitation (0–250 RPM), nitrogen sources (yeast, urea, ammonium chloride, and ammonium nitrate), and carbon sources (glucose, sucrose, starch, and dextrose). The qualitative analysis of the stored bio-lipids was performed using Fourier-transform infrared spectroscopy (FTIR) and Gas Chromatography Mass Spectrometry (GC–MS).Results and discussionThe maximum reactor performance was achieved with 40% lipid accumulation (gravimetric basis) in the dry cell biomass of Streptomyces sp. The results indicated the presence of C-H (Alkane), with additional phenolic and alcoholic bonds through FTIR, whereas the GC–MS results indicated the presence of palmitic acid and oleic acid as the most recurring compounds. This highlights the strong potential of Streptomyces sp. for biolipid based fuel production using sludge as a substrate. The contents of the extract (i.e., bio-lipids) were successfully transesterified to produce biofuels from the stored lipids. The findings indicated that the use of Streptomyces sp. potentially provides a dual benefit of reducing organic loading from the sludge along with biofuel production under optimized reactor conditions.